Understanding the Personality and Behavioral Mechanisms Defining Hypersexuality in Men Who Have Sex with Men. Issue 9 (1st September 2016) - Miner, Michael H.; Romine, Rebecca Swinburne; Raymond, Nancy; Janssen, Erick; MacDonald, Angus; Coleman, Eli
ABSTRACT: Introduction: Hypersexuality has been conceptualized as sexual addiction, compulsivity, and impulsivity, among others, in the absence of strong empirical data in support of any specific conceptualization. Aim: To investigate personality factors and behavioral mechanisms that are relevant to hypersexuality in men who have sex with men. Methods: A sample of 242 men who have sex with men was recruited from various sites in a moderate-size mid-western city. Participants were assigned to a hypersexuality group or a control group using an interview similar to the Structured Clinical Interview for the Diagnostic and Statistical Manual for Mental Disorders, Fourth Edition . Self-report inventories were administered that measured the broad personality constructs of positive emotionality, negative emotionality, and constraint and more narrow constructs related to sexual behavioral control, behavioral activation, behavioral inhibition, sexual excitation, sexual inhibition, impulsivity, attention-deficit/hyperactivity disorder, and sexual behavior. Main Outcome Measures: Hierarchical logistic regression was used to determine the relation between these personality and behavioral variables and group membership. Results: A hierarchical logistic regression controlling for age showed a significant positive relation between hypersexuality and negative emotionality and a negative relation with constraint. None of the behavioral mechanism variables entered this equation. However, a hierarchical multiple regression analysis predicting sexual behavioral control indicated that lack of such control was positively related to sexual excitation and sexual inhibition owing to the threat of performance failure and negatively related to sexual inhibition owing to the threat of performance consequences and general behavioral inhibition Conclusion: Hypersexuality was found to be related to two broad personality factors that are characterized by emotional reactivity, risk taking, and impulsivity. The associated lack of sexual behavior control is influenced by sexual excitatory and inhibitory mechanisms, but not by general behavioral activation and inhibitory mechanisms.